Resveratrol suppresses neuroinflammation to alleviate mechanical allodynia by inhibiting Janus kinase 2/signal transducer and activator of transcription 3 signaling pathway in a rat model of spinal cord injury - Han, Jie; Hua, Zhen; Yang, Wen-jie; Wang, Shu; Yan, Fang; Wang, Jun-nan; Sun, Tao (Frontiers in Molecular Neuroscience, 2023)
Background Neuropathic pain (NP) is one of intractable complications of spinal cord injury (SCI) and lacks effective treatment. Resveratrol (Res) has been shown to possess potent anti-inflammatory and anti-nociceptive effects. In this study, we investigated the analgesic effect of Res and its underlying mechanism in a rat model of SCI. Methods The rat thoracic (T10) spinal cord contusion injury model was established, and mechanical thresholds were evaluated during an observation period of 21 days. Intrathecal administration with Res (300 μg/10 μl) was performed once a day for 7 days after the operation. On postoperative day 7, the expressions of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) were determined by enzyme-linked immunosorbent assay (ELISA) and Real-time quantitative PCR (RT-qPCR), the expression of Janus kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3) signaling pathway was determined by western blot and RT-qPCR, and the co-labeled phospho-STAT3 (p-STAT3) with neuronal nuclear antigen (NeuN), glial fibrillary acidic protein (GFAP), and ionized calcium-binding adapter molecule 1 (Iba-1) were explored by double immunofluorescence staining in the lumbar spinal dorsal horns. The temporal changes of p-STAT3 were investigated by western blot on the 1st, 3rd, 7th, 14th, and 21st days after the operation. Results Intrathecal administration with Res for 7 successive days alleviated mechanical allodynia of rats during the observation period. Meanwhile, treatment with Res suppressed the production of pro-inflammatory factors TNF-α, IL-1β and IL-6, and inhibited the expressions of phospho-JAK2 and p-STAT3 in the lumbar spinal dorsal horns on postoperative day 7. Additionally, the protein expression of p-STAT3 was significantly increased on the 1st day following the operation and remained elevated during the next 21 days, immunofluorescence suggested that the up-regulated p-STAT3 was co-located with glial cells and neurons. Conclusion Our current results indicated that intrathecal administration with Res effectively alleviated mechanical allodynia after SCI in rats, and its analgesic mechanism might be to suppress neuroinflammation by partly inhibiting JAK2/STAT3 signaling pathway.